Charakterystyka działań marketingowych na rynku farmaceutycznym na przykładzie Hurtowni Farmaceutycznej CEFARM Rzeszów Oddział w Nowym Sączu - Wańczyk, Karolina (My University, 2011)
W pracy przedstawiono działania marketingowe na rynku farmaceutycznym. Badania prowadzone opierały się na analizie aktów prawnych, dostępnej literaturze i stadium przypadku indywidualnego. W pracy tej przedstawiłam najważniejsze podmioty działające na tym rynku, czyli: - producentów leków, - hurtownie farmaceutyczne, - apteki. Regulacje prawne i działania, które m.in. określają w sposób jasny: - jakie warunki na rynku farmaceutycznym muszą być spełnione, aby leki były dopuszczone do sprzedaży, - jakich działań trzeba przestrzegać, - kto nadzoruje te działania. Wszystkie działania marketingowe wykorzystywane w praktyce, by zwiększyć sprzedaż przez producentów leków, hurtowników i aptekarzy (reklama, promocja, telemarketing, obniżka cen, działania przedstawicieli farmaceutycznych) i ciągłe ulepszanie ich wskazują na wysoki stopień konkurencyjności na rynku farmaceutycznym.

The thesis discusses marketing activities in the pharmaceutical market. The research I conducted was based on the analysis of legal acts, available publications and an individual case study. The thesis presents: the most important subjects acting on the market, that is - drug manufacturers, - pharmaceutical warehouses, - chemists, legal regulations and activities, which among others clearly describe: - what requirements must be met for medicines to be approved for sale in the pharmaceutical market, - what activities must be undertaken, - who supervises such activities. All marketing activities used in practice to increase the sales of medicines by their manufacturers, warehouse owners and chemists (advertising, promotion, telemarketing, price reductions, the actions of pharmaceutical representatives) together with their constant improvement indicate a high level of competitiveness in the pharmaceutical market.
Marketing activities on pharmaceutical market on the example of CEFARM Rzeszów Pharmaceutical Warehouse Division in Nowy Sącz
Keywords: marketing; rynek farmaceutyczny; regulacje prawne; działania marketingowe w hurtowni farmaceutycznej; pharmaceutical market; legal regulations; marketing activities of a pharmaceutical warehouse